2019
DOI: 10.1016/j.resuscitation.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

2019 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations

Abstract: The International Liaison Committee on Resuscitation has initiated a continuous review of new, peer-reviewed, published cardiopulmonary resuscitation science. This is the third annual summary of the International Liaison Committee on Resuscitation International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. It addresses the most recent published resuscitation evidence reviewed by International Liaison Committee on Resuscitation Task Force sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
28

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 203 publications
0
114
0
28
Order By: Relevance
“…All EMS providers performed CPR according to the Japanese CPR guidelines, which are based on the International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. 8 Because EMS personnel in Japan are legally prohibited from terminating resuscitation in the field, most out-of-hospital cardiac arrest patients undergo EMS-provided CPR and are transported to hospitals, except in cases in which death is certain. The Fire and Disaster Management Agency recommends transporting out-of-hospital cardiac arrest patients to tertiary emergency medical centers.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…All EMS providers performed CPR according to the Japanese CPR guidelines, which are based on the International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. 8 Because EMS personnel in Japan are legally prohibited from terminating resuscitation in the field, most out-of-hospital cardiac arrest patients undergo EMS-provided CPR and are transported to hospitals, except in cases in which death is certain. The Fire and Disaster Management Agency recommends transporting out-of-hospital cardiac arrest patients to tertiary emergency medical centers.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…The recent ILCOR systematic review on compression to ventilation ratios for CPR identified no new evidence to guide in-hospital CPR that has been published since the previous review in 2015 [49,50].…”
Section: In-hospital Adult Cpr [15]mentioning
confidence: 99%
“…A recent meta-analysis has demonstrated the beneficial survival outcome DA-CPR [10]. The recent international consensus strongly recommends that emergency medical dispatch service centers have a proper system to support DA-CPR services [11]. DOI: http://dx.doi.org/10.5772/intechopen.91866…”
Section: Cpr (Dispatcher-assisted)mentioning
confidence: 99%